Psikophoria Untuk Remaja Rehabilitasi Narkoba di Sumatera Utara - Neni Triastuti (Jurnal Masyarakat Indonesia (Jumas), 2022)
There is a need for life skills in a social rehabilitation center for victims of narcotics, psychotropic and other addictive substances abuse, which so far have only been able to depend on third party funding sources. Victims of abuse of narcotics, psychotropics and other addictive substances are victims who have come close to even consuming narcotics, psychotropics and other addictive substances that are destroying the nation's generation. Drugs (narcotics, psychotropics and other addictive substances) can endanger human life, if consumed with inappropriate way, can even cause death (1) Drugs have a very broad negative impact; both physically, psychologically, economically, socially, culturally, defense and security, and so on (2).. Another Victim Social Rehabilitation Center "Insyaf" North Sumatra, which is approximately 36 km from the Medan LP3I Polytechnic, is a rehabilitation center for those who have consumed the illicit goods. Many methods are used so that drug users can return to normal and recover as usual, namely by keeping them busy so that they forget about the illicit goods. The problem that occurs is, after 9 months of the rehabilitation process, they leave and are returned to their respective families. However, 85% of those who have been sent home to their parents return to the rehabilitation center because they return to using these illicit goods.